Development and evaluation of 1’-acetoxychavicol acetate-loaded nanostructured lipid carrier for prostate cancer therapy / Bavani Subramaniam - Bavani , Subramaniam (2021)
Previous studies have established 1’-acetoxychavicol acetate (ACA), a phytoconstituent extracted from the rhizomes of Alpinia conchigera Griff (Zingiberaceae), as an anti-cancer compound with cytotoxic properties on many cancer types. ACA has been demonstrated to induce apoptosis-mediated cell death by deregulation of the NF-ĸB signalling pathway on cancer cells, while minimally affecting normal cells. However, as with other natural products, ACA is a hydrophobic ester with poor rate of dispersion, lack of bioavailability and non-specific tumour targeting in vivo. To overcome these problems, a nanostructured lipid carrier (NLC) system was formulated to encapsulate ACA and improve the latter’s aqueous solubility. In addition, to encourage targeted delivery towards tumours, the NLC was modified with AMD3100 octahydrochloride, an antagonist of the CXCR4 receptor which is overexpressed on many cancer cell lines. Formulation and optimisation of the NLC has availed nanoparticles of ideal physico-chemical properties which include small particle size, low aggregation tendency, high homogeneity, high affinity towards the drug, long-term stability and sustained rate of drug release. In vitro studies on PC-3 prostate cancer cells have also demonstrated time-based cellular uptake in addition to significant cytotoxicity, anti-migration and anti-invasion properties of the modified ACA-NLC. Furthermore, the ACA-NLC formulations have exhibited significant anti-tumour efficacy in nude athymic (Nu/Nu) mice models. The lack of systemic toxicity such as loss in body weight and inflammation of major organs, suggest the safety of the lipid excipients towards the biological system. Post-in vivo immunohistochemistry analysis and cytokine quantification provided evidence that the NLCs downregulated NF-ĸB related tumour markers and pro-inflammatory cytokines. Therefore, this NLC system was found to have great potential in promoting the anti-tumour effects of ACA in prostate cancer therapy and can possibly be translated to other forms of cancer.